2013
DOI: 10.3390/nu5072530
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Probiotic Strains in Caries Prevention: A Systematic Review

Abstract: This paper aims to provide a systematic review of the caries-prevention effect of probiotics in human. The hypothesis was that the administration of probiotic strains might play a role in caries lesion prevention and in the control of caries-related risk factors. The main relevant databases (Medline, Embase) were searched. Quality of the Randomized Clinical Trials (RCTs) was classified using the “Consolidated Standards of Reporting Trials” (CONSORT) checklist and the Impact Factor (IF) value of each journal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
110
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 83 publications
(208 reference statements)
2
110
0
4
Order By: Relevance
“…Although many studies have explored the use of LAB for the benefit of oral health, there are currently no comprehensive or standardized in vitro protocols for screening novel oral probiotics [5,13,23]. Probiotic candidates have been routinely screened based on their ability to survive in an artificial host barrier system such as with stimulation of gastric acid or enzymatic stresses [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies have explored the use of LAB for the benefit of oral health, there are currently no comprehensive or standardized in vitro protocols for screening novel oral probiotics [5,13,23]. Probiotic candidates have been routinely screened based on their ability to survive in an artificial host barrier system such as with stimulation of gastric acid or enzymatic stresses [4].…”
Section: Discussionmentioning
confidence: 99%
“…These effects are thought to be exerted via enhancement of intestinal functions or inhibition of metabolic diseases caused by intestinal dysbiosis [3,4]. Despite the fact that the oral cavity is the first point of contact between probiotics and the host system [5], few studies have directly investigated the effects of probiotics on the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies showed that probiotic strains may affect the oral ecology by preventing the adherence of other bacteria to saliva-coated hydroxyapatite and by modifying the composition of the salivary pellicle (16). Other mechanisms of action for probiotics on oral health are described in literature, including adhesion, co-aggregation, competitive inhibition, production of organic acids and bacteriocin-like compounds and immune-modulation (17). In particular, the enhanced resistance to oral infections could be obtained through the interaction among probiotics, oral epithelium and saliva.…”
Section: Discussionmentioning
confidence: 99%
“…36 The focus on these species is due to their production in the dairy industry, showing a symContreras P, Kay J, Burgos C, Contreras C & Huber H.…”
Section: 35mentioning
confidence: 99%